The Perception of Grade 12 General Academic Strand on Their Strand Towards Their College Track: Vol.4, No.1 (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
The graduating senior high school students from General Academic Strand face problemschoosing their college track. The purpose of this study is to identify the perception of Grade 12General Academic Strand on their strand towards their college track and how the males andfemales assessed their career choice in terms of knowledge, skills, and career orientation whocurrently enrolled in Bestlink College of the Philippines school year 2022-2023.It reveals that male and female respondents agree that the General Academic Strand helpsthe Grade 12 students' future careers regarding knowledge, skills, and career orientation. Thisstudy revealed that the null hypothesis is accepted. There is no significant difference betweenthe assessments of the two groups of respondents in terms of knowledge and skills. Still, thenull hypothesis was rejected because there was a significant difference in the assessment ofthe two groups in terms of career orientation.The General Academic Strand students should apply the knowledge acquired in the GeneralAcademic Strand for choosing a career; they also should consider the skills acquired in theGeneral Academic Strand for choosing a career, and the General Academic Strand shouldconsider the experiences gained in the General Academic Strand choosing a career.
Keywords: Education